Very large haematoma following the nonoperative management of a blunt splenic injury in a patient with preexisting liver cirrhosis: a case report - Euisung Jeong; Younggoun Jo; Yunchul Park; Jungchul Kim; Hyunseok Jang; Naa Lee (Journal of Trauma and Injury)
The spleen is the most commonly injured organ after blunt abdominal trauma. Nonoperative management (NOM) is the standard treatment for blunt splenic injuries in haemodynamically stable patients without peritonitis. Complications of NOM include rebleeding, new pseudoaneurysm formation, splenic abscess, and symptomatic splenic infarction. These complications hinder the NOM of patients with blunt splenic injuries. We report a case in which a large haemorrhagic fluid collection that occurred after angio-embolisation was resolved by percutaneous drainage in a patient with liver cirrhosis who experienced a blunt spleen injury.